Phytochemistry, pharmacology and perceived health uses of non-cultivated vegetable Cyphostemma adenocaule (Steud. ex A. Rich.) Desc. ex Wild and R.B. Drumm: A review - Oluwasesan Micheal Bello; Safiya Muhammad Jagaba; Oluwatoyin Eunice Bello; Abiodun Busuyi Ogbesejana; Oluwasogo A. Dada; Charles Oluwaseun Adetunji; Saudat Muhammad Abubakar (Scientific African, 2019)
Vegetables have been one of the often recommended and cheap solution to the undernourishment/malnourishment challenge experienced worldwide. Beside the cultivated and exotic vegetables, there are greater number of non-cultivated and wild edible plants’ species. Documenting and revalorizing these neglected vegetables is a must and growing trend these days. The thrust of this study is to offer and give up-to-date knowledge cum perceive health uses of one of these edible plant species called Cyphostemma adenocaule (Steud. ex A. Rich.). This study clearly showed that C. adenocaule is a non-cultivated vegetable eaten by most countries in Africa. Empirical facts about the nutritional advantage inherent in this edible plant is scarce, more studies are needed to establish its functionality. There are enormous records of traditional uses of this wild vegetable though the biological and pharmacological evidences are very few, there is urgent need to justify this claims. Phytochemistry studies is scanting, showing twelve compounds mostly are ceanothane-type triterpenoids, have been isolated so far including some polysaccharide. This review tends to gather works till date on this plant so as to provide enough information for future research hence it is clear that the phytochemistry of this plant is yet to be explored fully. Keywords: Deworming, Non-cultivated, Cyphostemma adenocaule, Vegetable, Phytochemistry